Promoting Transparency and Civil Engagement through the Impacts of ICT and Social Media: A Case Study of Pagadian City - Yray, Earl Jhon Restor; Nurmandi, Achmad; Younos, Muhammad (JURNAL ILMU SOSIAL, 2025)
With cities across Philippines and the world transitioned to E-governance, Pagadian City shifted to and adapted the concept if e-government with the help of social media and ICT in general. Like any other cities where social media was the main portal to promote transparency and civil engagement, this paper will give data on how ICT and social media made an impact to promote transparence and civil engagement. Using qualitative research method, this paper analyzed the data from Asenso Pagadian page of Pagadian City on how citizens adapted this paradigm shift from the usual transparency boards. As a result, it shows that citizens were comfortable with the shift to e-governance where data and information is just in the tip of their fingers to engage with the city’s processes and programs.